Construção, calibração e análise de desempenho de um piranômetro de baixo custo, baseado no modelo Kimball-Hobbs - Naziazeno, Ronaldo Nascimento (2009)
In this work a pyrometer using the classic model of Kimball-Hobbs was developed, tested and calibrated. The solar radiation is verified through the temperature difference between the sensible elements covered by absorbing (black) and reflecting (white) pigmentations of the incoming radiation. The photoacoustic technique was used to optimize the choice of the pigments. Methodologies associated with linearity, thermo-variation, sensibility, response time and distance are also presented. To correctly classify the results, the international standard ISO 9060 as well as indicative parameters of World Meteorological Organization (WMO) are used. In addition a system of data acquisition of two channels with 12 bits, constructed during the this time, was used to measure the global solar radiation on the ground by the pyrometer and also by another pyrometer certified in the case of Keep & zonen. The results statistically show, through the hypothesis test presented here, that both equipments find population average with 95% of correctness